The Gentleman Outlaw and me--Eli : a story of the Old West - Hahn, Mary Downing (New York : Clarion Books, 1996)
In 1887 twelve-year-old Eliza, disguised as a boy and traveling towards Colorado in search of her missing father, falls in with a Gentleman Outlaw and joins him in his illegal schemes.
Keywords: Frontier and pioneer life -- West (U.S.) -- Fiction; Robbers and outlaws -- Fiction; West (U.S.) -- Fiction